Digital Learning for Religious Moderation: Assessing the Impact of MOOCs on Understanding Wasathiyah Islam - Muhamad Maulana; Fitri Amalia; Nafisah; Nabila Nindya Alifia Putri; Destina Wahyu Winarti (UIII Press, 2026)
This study examines the impact of Massive Open Online Courses (MOOCs) in improving students' understanding of Wasathiyah Islam, a concept that calls for balance and moderation in Islamic teachings. With the growing number of religious extremism and intolerance, the issue of religious moderation has become prominent, as it is a basis for promoting tolerance, peace, and cooperation among diverse communities. However, there is a lack of empirical research investigating the impact of online learning, like MOOCs, on promoting religious moderation. To fill this gap, this study applied a quantitative approach using pretest and posttest analysis to measure participants' knowledge enhancement. The results showed a significant improvement of students' understanding, with a pretest logit score of 0.63 increasing to a posttest logit score of 4.45. Although the high standard deviation—the dispersion was relatively high, which indicated that most students' comprehension levels vary—Wilcoxon Signed Rank Test validated a statistically significant improvement: Z = -4.675, p < 0.001. This improvement score confirms the effectiveness of the MOOC in enhancing students’ understanding of Wasathiyah Islam. Further, data based on the Likert scale indicated mean scores increasing from 31.81 to 43.03, with 28 out of 32 showing improvement. These findings underline the potential of MOOCs as strong tools for strengthening religious moderation and suggest that through e-learning, societies could be more knowledgeable and peaceful—thus overcoming most of the current challenges of intolerance and extremism.